Security is like oxygen: Evidence from Uganda - Zhang, Xiaobo (International Food Policy Research Institute, 2004)
Since the early 1990s, Uganda has been one of Africa's fastest growing countries. However, at the sub-national level, growth has been uneven due to civil conflict in the northern region. Using a panel of household and community level data, this paper examines the links between security and economic growth. It is found that security is a pre-condition for successful economic development and that there is in fact a threshold level of security below which public investments in infrastructure and education have little impact on growth. Only when security exceeds this threshold do public investments stimulate economic growth. Economists and policy advisors living in peaceful countries often prescribe economic policies that hinge on the assumption of good security. In this manner, security, like oxygen, is taken for granted. -- Authors' Abstract